The translation of rhetorical questions in the holy Quran into English / Ibrahim I.I. Najjar - Ibrahim I.I., Najjar (2020)
The current study deals with Quranic rhetorical questions that carry specific rhetorical functions and their two English translations. The analysis is based on twenty four Quranic rhetorical questions and their two English translations: “the Koran Interpreted” by Arberry (1955/1996) and “the Noble Quran: English translation of the meanings and commentary” (1996) by al-Hilali and Khan. The study aims to (1) find out the types of grammatical shifts that have occurred in the two English translations (2) examine the effects of such shifts on the context of situation especially tenor and mode of the rhetorical questions translated into English. To achieve the first objective, Haegeman’s (2006) x bar theory and Catford’s (1965) translation shifts are employed. In this situation, firstly, the source text (ST) and two target texts (TTs) are syntactically analysed to uncover the grammatical shifts; secondly, such shifts are classified according to Catford’s (1965) shifts in translation. For the second objective, Halliday and Hasan’s (1985) and Halliday’s (1994) context of situation especially tenor and mode are focused upon. In this context, their associated language metafunctions, i.e. interpersonal metafunction and textual metafunction are investigated. The study shows different types of grammatical shifts in the two English translations. Besides, syntactic shifts have also appeared. The study shows that grammatical shifts do affect the tenor and mode of the Quranic rhetorical questions translated into English. Apart from maintaining the tenor and mode in both translations in some instances, they have been affected slightly, partially and fully in some others. Consequently, the functions of the Quranic rhetorical questions have been affected. The tenor of discourse is both interesting and important as it enables us to understand and differentiate among/between the participants’ roles and relationship in the ST and TTs RQs. The analysis shows that the change of the participants’ relationship and roles will affect the message conveyed.